Pesantren Tarekat dalam Spirit Patriotisme Para Bandit Pedesaan pada Era Penjajahan Belanda (Studi Kasus di Distrik Goranggareng, Kabupaten Magetan, 1900–1935) - Adhie Handika Restu Damara; Wasis Nur Aini (Medan Resource Center, 2026)
Dutch colonial rule in Indonesia extended to Goranggareng District, Magetan Regency, where the imposition of a trade monopoly intensified economic hardship and contributed to rising social unrest and criminality in the early twentieth century. At the same time, the region was marked by the presence of several pesantren affiliated with Sufi orders that combined spiritual instruction with elements of martial discipline. This study investigates how these religious institutions shaped local social dynamics and responded to colonial domination between 1900 and 1935. Employing a qualitative social-historical approach, the research draws on archival records, Dutch-language newspapers, contemporaneous publications, and relevant scholarly works, analyzed through heuristic procedures, source criticism, and interpretative reconstruction. The findings demonstrate that Sufi-oriented pesantren played a pivotal role in cultivating moral solidarity, reinforcing communal identity, and providing a spiritual framework that legitimized forms of localized resistance. Rather than functioning merely as educational institutions, these pesantren operated as socio-religious networks that transformed marginalized actors into agents of anti-colonial patriotism. The article argues that the interplay between religious authority and subaltern resistance constituted a significant, though often overlooked, dimension of rural opposition to Dutch colonial power in Goranggareng.